2022
DOI: 10.3389/fneur.2022.1008310
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of obstructive sleep apnea treatment by antileukotriene receptor and surgery therapy in children with adenotonsillar hypertrophy: A descriptive and cohort study

Abstract: BackgroundPrevalence of obstructive sleep apnea (OSA) in children with adenotonsillar hypertrophy is high and related to the occlusion of the upper airway. The main treatments of OSA in these children is adenotonsillectomy. However, this intervention is an invasive method with a various success rate. Thus, the indications of tonsillectomy remain debatable and non-invasive treatment is still a potential choice in these patients.MethodsIt was a cross-sectional and interventional study. This study included childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
3
1
1
Order By: Relevance
“…In the present study, only a few children with overweight or obese in the asthma group with OSA ( Table 2 ). This result was different from other studies in Western countries, which showed that high BMI increased the prevalence of OSA ( 3 , 4 , 13 ), but similar to other Vietnamese studies ( 16 , 31 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, only a few children with overweight or obese in the asthma group with OSA ( Table 2 ). This result was different from other studies in Western countries, which showed that high BMI increased the prevalence of OSA ( 3 , 4 , 13 ), but similar to other Vietnamese studies ( 16 , 31 ).…”
Section: Discussioncontrasting
confidence: 99%
“…OSA was considered as a risk for the presence of ADHD (OR: 3.355; 95% CI: 1.271–8.859; p < 0.05), rather than asthma control ( Figure 4 ). This result was similar to other studies ( 31 , 35 ). Moreover, OSA + ADHD group had a markedly higher AHI score and significantly lower saturation oxygen than the OSA-alone group.…”
Section: Discussionsupporting
confidence: 94%
“…Instrumental examinations useful for diagnosis include lateral neck X-ray, videofluoroscopy, and nasal endoscopy; nasal endoscopy performed by the otolaryngologist represents the gold standard [16,17]. Tonsillar hypertrophy is measured with Brodsky's grading scale [18]: grade 0, tonsils confined in tonsillar fossa; grade 1, oropharyngeal width occupied less than 25%; grade 2, occupied between 26 and 50%; grade 3, occupied between 51 and 75%; and grade 4, occupied more than 75% [18,19]. Likert's classification is used for adenoid hypertrophy [20].…”
Section: Adenotonsillar Hypertrophymentioning
confidence: 99%
“…However, tonsil size is slightly related to AHI, and thus with the severity of OSA [25,26]. Tonsil hypertrophy of 25-50% may lead to a two-fold increase in OSA development, hypertrophy of 50-75% to a three-fold increase, and hypertrophy of 75-100% up to an eight-fold increase [19]. An adenoidectomy and tonsillectomy are the first-line treatment for AH.…”
Section: Adenotonsillar Hypertrophymentioning
confidence: 99%
“…However, this intervention is an invasive method for children with asthma ( 1 ). Some recent reported showed that tonsillar tissue from children with OSA may overexpress cysteine leukotriene receptor-1 (CysLT1), which can be treated with anti-inflammatory therapy such as leukotriene receptor antagonists ( 10 , 11 ). In children with non-severe OSA, this therapy might have the potential efficacy in the treatment of asthmatic children with OSA associated with adenotonsillar hypertrophy ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%